Teaching continuing training for the use of ICT in the teaching and learning process (Research, Society and Development, 2020)
This article discusses the use of digital technologies as educational tools in the school space, and how continuing education initiatives are relevant in this regard. Aspects involving these initiatives and the contextualized use of digital technologies are discussed, so that these technologies help in the development of learning environments, enriching them, making them dynamic, stimulating and challenging for students, favoring active learning and autonomous. Thus, this article aimed to analyze the importance and the relationship between the continuing education initiatives of teachers for the pedagogical use of Information and Communication Technologies (ICT) in the teaching and learning process. The research, quantitative case study type, developed from the completion of a continuing education course for elementary school teachers in the public school of Santo Antônio de Padua, Rio de Janeiro, where ICT-related aspects were addressed. as educational technologies. The observed data, measured through the analysis of questionnaires applied to teachers, demonstrated the relevance of such initiatives as an opportunity for reflection and updating of education professionals regarding the use of ICT in the school context, recognizing them as potentializing and enriching instruments of the process. teaching and learning.